2022
DOI: 10.1111/imb.12760
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Lnc_209997 suppresses Bombyx mori nucleopolyhedrovirus replication by targeting miR‐275‐5p in B. mori

Abstract: Long non‐coding RNA (lncRNA) is a type of non‐coding RNA molecule, which exceeds 200 nucleotides in length and participates in the regulation of a variety of life activities. Recent studies showed that lncRNAs play important roles in viral infection and host immunity. At present, the researches on insect lncRNAs are relatively few. In this study, we found the expression of Lnc_209997 was significantly down‐regulated in silkworm fat body infected with Bombyx mori nucleopolyhedrosis virus (BmNPV). Inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The role of lncRNAs in insect immunity and permissiveness to pathogens has been investigated in other species, particularly D. melanogaster, for which significant findings regarding its immune response against pathogenic viruses and bacteria have been reported [15,43,44]. Research has also been carried out in lepidopteran species such as Bombyx mori and Pectinophora gossypiella, in which specific lncRNAs have been implicated in the response to viral infection [45,46]. Despite the progress made in other species, lncRNA research in mosquito species has until now been limited and their implication in vector competence and immune responses to human pathogens has not been extensively addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The role of lncRNAs in insect immunity and permissiveness to pathogens has been investigated in other species, particularly D. melanogaster, for which significant findings regarding its immune response against pathogenic viruses and bacteria have been reported [15,43,44]. Research has also been carried out in lepidopteran species such as Bombyx mori and Pectinophora gossypiella, in which specific lncRNAs have been implicated in the response to viral infection [45,46]. Despite the progress made in other species, lncRNA research in mosquito species has until now been limited and their implication in vector competence and immune responses to human pathogens has not been extensively addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results indicated that after infection with BmNPV, the silkworm could regulate its self-immunity through the lncRNA-miRNA-mRNA pathway ( Zhang S. et al, 2020 ). In the fat body, Lnc_209997 was significantly down-regulated in BmNPV-infected silkworms, and Lnc_209997 could also inhibit BmNPV replication by regulating miR-275-5p expression ( Lin et al, 2022 ). Therefore, to promote its replication in vivo , BmNPV reduced the expression of host Lnc_209997 and indirectly regulated miR-275-5p ( Lin et al, 2022 ).…”
Section: Regulation Of Bmnpv Infection In the Silkworm By Ncrnasmentioning
confidence: 99%
“…In the fat body, Lnc_209997 was significantly down-regulated in BmNPV-infected silkworms, and Lnc_209997 could also inhibit BmNPV replication by regulating miR-275-5p expression ( Lin et al, 2022 ). Therefore, to promote its replication in vivo , BmNPV reduced the expression of host Lnc_209997 and indirectly regulated miR-275-5p ( Lin et al, 2022 ). Since these studies, the function of lncRNA is becoming better understood.…”
Section: Regulation Of Bmnpv Infection In the Silkworm By Ncrnasmentioning
confidence: 99%
“…It is well documented that a growing number of insect lncRNAs exert roles in insect immune, however, few in‐depth functional analyses of lncRNA are available in B. mori . Lin et al (2022) found silkworm Lnc_209997 could suppress BmNPV replication by targeting miR‐275‐5p in B. mori , implying lncRNA may play a role in the immune response of silkworm. LncRNA4 showed a similar expression pattern to that of Toll 4 and could be used as a bait to titrate the dimer of Toll, which is required for the production of antimicrobial peptides (Satyavathi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%